PENGARUH PENAMBAHAN LIMBAH PLASTIK JENIS THERMOSETTING TERHADAP MUTU BATA RINGAN (HEBEL) - Supriyadi, Supriyadi; Kusdiyono, Kusdiyono; Wahyono, Herry Ludiro; Utomo, Marchus Budi; Nurhadi, Imam (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
At this time, plastic is a material that is needed by the wider community and its impact is also extraordinary after the plastic is used in everyday life which can cause serious problems if the management is not done properly. The problem of plastic waste does not only occur in the city of Semarang, but also in other cities, so that the Ministry of Environment and Forestry to impose a program to use paid plastic bags in the short term. But this is only to deal with problems in the short term. In the long run, it will not solve the problem of "plastic waste", because the policy actually encourages people to buy plastic which, of course, will add a new burden on the community to buy it. The results showed that the compressive strength of light brick with the model / type of BN s.d. B10.0 with 10 variations of the mixture of the addition of plastic waste starting from (1.0 to 10.0)% to the weight of Portland Cement (PC) there is a decrease in the average compressive strength. The lowest was the addition of 10.0% plastic waste with an average compressive strength of 9.88 kg / cm². The regression equation obtained Y = 0.042 X ² - 1.177 X + 18.84 with a correlation value R ² = 0.934, meaning that the addition of plastic waste ranging from (1.0 to 10.0)% of the weight of Portland Cement (PC) has the effect of "very strong "against the compressive strength. So we can get a picture that by adding the addition of plastic waste affects the compressive strength decreases. So that it can be investigated with other compositions by adding Fly Ash and sand made with a mixture ratio of 1 PC: 2 Aggregate (Sand and Fly Ash), with the hope that this Fly Ash waste can also be used for lightweight brick building elements